2013
DOI: 10.5296/ajfa.v5i1.2864
|View full text |Cite
|
Sign up to set email alerts
|

Lean Manufacturing Practices and Environmental Performance in Malaysian Automotive Industry

Abstract: Toyota Production System (TPS) a systematic approach to identify and eliminate waste activities through continuous improvement and understand the principles of lean such as identification of value, elimination of waste and generation of flow (of value to the customer). This paper explores between lean manufacturing practices (supplier management, employee involvement, just in time, customer focus and statistical process control to monitor quality) and environmental performance outcomes (operational and innovat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Nevertheless, although green practices can fulfil the market's greener expectations by extending the "waste reduction" idea proposed by lean manufacturing, in the sense of reducing waste, pollution, raw material usage and energy consumption, the relationship between green practices and the economic performance remains unclear. On one hand, there are researchers that agree that green strategies, such as Design for Environment (DfE) or Green Supply Chain Management (GSCM), optimise the interaction of the economic and the environmental systems, producing a sustainable development and enterprise integration [15][16][17][18]. On the other hand, there are researchers that state that green practices are not enough to ensure sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, although green practices can fulfil the market's greener expectations by extending the "waste reduction" idea proposed by lean manufacturing, in the sense of reducing waste, pollution, raw material usage and energy consumption, the relationship between green practices and the economic performance remains unclear. On one hand, there are researchers that agree that green strategies, such as Design for Environment (DfE) or Green Supply Chain Management (GSCM), optimise the interaction of the economic and the environmental systems, producing a sustainable development and enterprise integration [15][16][17][18]. On the other hand, there are researchers that state that green practices are not enough to ensure sustainability [19].…”
Section: Introductionmentioning
confidence: 99%
“…For this particular parameter, the framework consisting functionalism as well as the fundamental humanism and structuralism was employed, and based on these research approaches the reviewed studies are categorized as below: Liu et al (2014) developed a non-dominant sorting genetic algorithm to attain Pareto front and to diminish total non-processing electricity consumption as well as the total weighted delay in a job shop; Ahemad et al (2013) highlighted the weak areas as potential for company to improve green manufacturing execution through case study in Indian steel industry; Elsayed et al (2013) discussed a 3-step approach for proactive performance assessment of green-lean through case study in an automotive, resulting 10.8% drop in production cost; Salleh et al (2012) studied the green lean total quality information management system via questionnaire in 30 automotive vendors in Malaysia; Esmer et al (2010) intended to find out the optimal number of handling equipment & reduced the ecological harm of Turkish container terminal via a simulation model; Abdulmalek and Rajgopal (2007) applied the value stream mapping (VSM) & simulation model to contrast the before & after state in an integrated steel mill; Purvis et al (2014) explored the flexibility in context of lean, agile & leagile supply networks and investigated the vendor & sourcing flexibility in two UK based specialist fashion retailers; Vivek and Ravindran (2008) emphasized the impact of environmental uncertainty on the lean practices followed by small manufacturing firms; Satao et al (2012) reviewed on how green manufacturing can be achieved through lean in order to prevent pollution & protect environment. Roosen and Pons (2013) offered a method to integrate environmental waste into lean through VSM in manufacturing setting for carbon footprint; Omer (2008) reviewed the literature on energy sources, environment & sustainable development for reducing fossil energy use and to promote the green energies in construction sector; Venkat and Wakeland (2006) investigated the environmental performance for CO 2 emissions using simulation model and suggested that it is quite possible for lean & green to be in clash that leads to tradeoffs and further chances for optimization; Hibadullah et al (2013) explored the relationship between lean and environmental performance in Malaysian automotive industry by structural equation modelling (SEM); Yang et al (2010) hypothesized that environmental management is partially an extension of advanced manufacturing practices and found that the electronic & electrical industries in China & Taiwan have developed their own practices; Herron and Hicks (2008) disseminated the selected lean techniques in companies of north-east England to improve productivity and obtained the savings as eight times greater than total costs from 15 companies; …”
Section: Grouping 4: Research Approachesmentioning
confidence: 99%
“…Schoenherr (2011) hypothesised the impact of EN on plant performance. Environmental initiatives considered include ISO 14000 certification, pollution prevention, recycling of materials, and waste reduction (Hibadullah et al 2013); plant performance is assessed with the dimensions of the four competitive capabilities of quality, delivery, flexibility, and cost. Yang et al (2011) suggest that prior lean manufacturing experiences are positively related to EN practices.…”
Section: Manufacturing Processes (Mp)mentioning
confidence: 99%